Evaluation of Acute Enteritis Cases in Adults Presenting to the Emergency Department: A Single Tertiary Care Hospital Experience - Tufan Tükek; Alpay Medetalibeyoğlu; Barış Emekdaş; Kaan Akın; Hilal Senkal; Merve Guzel Dirim; Naci Şenkal (Sakarya Tıp Dergisi)
Introduction: Acute enteritis can occur due to numerous bacterial, viral, and parasitic infections. This clinical condition can have various spectra in vulnerable patient groups with immunodeficiency and inflammatory bowel disease. This study aimed to examine cases of acute enteritis in the emergency unit of a tertiary-care hospital.Material and Methods: This cohort study was conducted with consecutive patients between September 2022 and November 2023. The clinical, laboratory, and microbiological data of the 194 patients were retrospectively examined. Patients with immunocompromised (IC) or inflammatory bowel disease (IBD) were analyzed in a healthy population. Results: The mean age of patients was 47 ± 19 (19 - 91). One-third of the patients had IC, and in the stool analysis, leukocytes and blood were positive in one-third and one-twentieth of the patients, respectively. Only one-tenth of patients had positive stool culture results. IC patients presented with metabolic acidosis, increased creatinine levels, and acute-phase reactant levels. Despite the lower prevalence of leukocytes and blood in stool samples, culture positivity was higher in IC patients.Conclusion: Stool culture positivity was low for the diagnosis of acute enteritis. Culture examination is important in IC patients, even in the absence of direct microscopic findings. Because patients with IC are more susceptible to complications, clinical assessment is important.